MARINE ECOTOURISM DEVELOPMENT STRATEGY OFPELAWAN BEACH KARIMUN REGENCYRIAU ARCHIPELAGO PROVINCE - Anggit Wondy Satrio; Dessy Yoswaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was carried out in March – April 2018, aiming to find out the potential of ecotourism in coastal marine Peawanto developed as the area of ecotourism, and analyzing marine development strategy of ecotourism in coastal marine PelawanThe Karimun Regency. The method used is the method the survey. The data collected includes the opinions of respondents, ecotourism activities identification and measurement of the quality of the water. The results of this research show the Pelawan Beach  has the potential to be developed as an ecotourism district. Pelawan Beach included in category S1 (very appropriate) with index value conformity of ecotourism at the station I (87.82%), II (83.33%), III (85.25%). The results of the SWOT analysis suggests some alternative management strategies that are appropriate for the development of ecotourism in coastal marine Pelawan, analysis consists of three priorities, namely: 1) spatial and territorial zoning system by forming for nautical tourism activities and community activities conducted against activities of marine ecotourism and coastal environmental management, 2) created the national as well as international promotions and 3) harnessing the potential of natural resources, culture, aksebilitas region to attract visitors through the construction and development of marine ecotourism with the concept of ecotourism through a promotion.  .             Key Words: Potential For Ecotourism, Nautical, SWOT Analysis,                Pelawan Beach.